Determination of moisture transfer coefficient in building materials on the basis of kinetics of a one direction capillary rise = Wyznaczenie współczynnika przenoszenia wilgoci w materiałach budowlanych na podstawie danych o kinetyce jednokierunkowego podciągania kapilarnego - Alsabry, Abdrahman (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents an original mathematical presentation and calculation procedure to determine a moisture transfer coefficient in building materials on the basis of kinetics of a one direction capillary rise.
Keywords: współczynnik przenoszenia wilgoci; podciąganie kapilarne; transport wilgoci; modele matematyczne; moisture transport goefficient; capillart rise; capillart transport; mathematical model